A Genetic Study of Spillovers in the Bean Common Mosaic Subgroup of Potyviruses - Hajizadeh, Mohammad; Ben Mansour, Karima; Gibbs, Adrian J (Viruses, 2024)
Nine viruses of the bean common mosaic virus subgroup of potyviruses are major international crop pathogens, but their phylogenetically closest relatives from non-crop plants have mostly been found only in SE Asia and Oceania, which is thus likely to be their "centre of emergence". We have compared over 700 of the complete genomic ORFs of the crop pandemic and the non-crop viruses in various ways. Only one-third of crop virus genomes are non-recombinant, but more than half the non-crop virus genomes are. Four of the viruses were from crops domesticated in the Old World (Africa to SE Asia), and the other five were from New World crops. There was a temporal signal in only three of the crop virus datasets, but it confirmed that the most recent common ancestors of all the crop viruses were before inter-continental marine trade started after 1492 CE, whereas all the crown clusters of the phylogenies are from after that date. The non-crop virus datasets are genetically more diverse than those of the crop viruses, and Tajima's D analyses showed that their populations were contracting, and only one of the crop viruses had a significantly expanding population. dN/dS analyses showed that most of the genes and codons in all the viruses were under significant negative selection, and the few that were under significant positive selection were mostly in the PIPO-encoding region of the P3 protein, or the PIPO protein itself. Interestingly, more positively selected codons were found in non-crop than in crop viruses, and, as the hosts of the former were taxonomically more diverse than the latter, this may indicate that the positively selected codons are involved in host range determination; AlphaFold3 modelling was used to investigate this possibility.
Keywords: molekulární evoluce; Open Reading Frames; protein modelling; Potyvirus; Phylogeny; Plant Diseases; Evolution, Molecular; genom virový; potyvirus; genetická variace; Genetic Variation; Crops, Agricultural; Genome, Viral; fylogeneze; emergences; nemoci rostlin; otevřené čtecí rámce; spillovers; population genetics; phylogenetics; zemědělské plodiny; codon selection